Emergency Medicine Residency Applicants’ Perceptions about Being Contacted after Interview Day - Yarris, Lalena M (Western Journal of Emergency Medicine, 2010)
Objective: We sought to characterize the experiences and preferences of applicants to emergency medicine (EM) residency programs about being contacted by programs after their interview day but before the rank list submission deadline.Methods: This cross-sectional study surveyed all applicants to an academic EM residency during the 2006-2007 interview cycle. Participation was anonymous and voluntary. We used a Web-based survey software program to administer the survey in February 2007, after rank lists were submitted. Two additional invitations to participate were sent over the next month. The instrument contained multiple-choice and free-text items. This study was submitted to our Institutional Review Board and was exempt from formal review.Results: 240/706 (34%) of applicants completed the survey. 89% (214/240) of respondents reported being contacted by a residency program after their interview but before rank lists were due. Of those contacted, 91% report being contacted by e-mail; 67% by mail; and 55% by phone. 51% of subjects reported that being contacted changed the order of their rank list in at least one case. A majority of contacted applicants felt “happy” (58%) or “excited” (56%) about being contacted, but significant numbers reported feeling “put on the spot” (21%) or “uncomfortable” (17%). A majority felt that it is appropriate for programs to contact applicants after interview day but before the rank lists are submitted, but 39% of contacted subjects responded that contact by phone is either “always inappropriate” or “usually inappropriate.” Regarding perceptions regarding the rules of the match, 80% (165/206) of respondents felt it was appropriate to tell programs where they would be ranked, and 41% (85/206) felt it was appropriate for programs to notify applicants of their place on the program’s rank list.Conclusion: Most EM residency applicants report being contacted by programs after the interview day but before rank lists are submitted. Although applicants feel this practice is appropriate in general, over a third of subjects feel that contact by phone is inappropriate. These findings suggest that residency programs can expect a majority of their applicants to be contacted after an interview at another program, and shed light on how applicants perceive this practice. [West J Emerg Med. 2010; 11(5):474-478.]